Molecular survey of canine parvovirus type 2: the emergence of subtype 2c in New Zealand - Dunowska M; Bain H; Bond S (Taylor and Francis Group on behalf of the New Zealand Veterinary Association, 2025)
AIMS: To determine the genetic makeup of carnivore parvoviruses currently circulating in New Zealand; to investigate their evolutionary patterns; and to compare these viruses with those detected during the previous New Zealand-based survey (2009-2010). METHODS: Faecal samples from dogs (n = 40) with a clinical diagnosis of parvovirus enteritis were voluntarily submitted by veterinarians from throughout New Zealand. In addition, one sample was collected from a cat with comparable clinical presentation. The samples were used for DNA extraction and PCR amplification of viral protein 2 (VP2) of canine parvovirus type 2 (CPV-2). All samples produced amplicons of the expected sizes, which were then sequenced. The viruses were subtyped based on the presence of specific amino acids at defined locations. In addition, VP2 sequences were analysed using phylogeny and molecular network analysis. RESULTS: The majority (30/40; 75%) of CPV-2-infected dogs were younger than 6 months and 8/40 (20%) were aged between 9 months and 1 year. Most (39/41; 95%) parvoviruses were subtyped as CPV-2c, and one as the original CPV-2. The faecal sample from a cat was positive for feline panleukopenia virus. The majority (37/39; 95%) of New Zealand CPV-2c viruses were monophyletic. The remaining two New Zealand CPV-2c viruses clustered with Chinese and Sri Lankan CPV-2c viruses, separately from the main New Zealand clade. CONCLUSIONS: There has been an apparent replacement of the CPV-2a viruses with CPV-2c viruses in New Zealand between 2011 and 2019. The source of the current CPV-2c viruses remains undetermined. The monophyletic nature of the majority of viruses detected most likely reflects a country-wide spread of the most successful genotype. However, an occasional introduction of CPV-2 from overseas cannot be excluded. CLINICAL RELEVANCE: Current vaccines appear to be protective against disease caused by the CPV-2c viruses currently circulating in New Zealand. Vaccination and protection from environmental sources of CPV-2 until the development of vaccine-induced immunity remains the cornerstone of protection in young dogs against parvovirus enteritis. Ongoing monitoring of the genetic changes in CPV-2 is important, as it would allow early detection of variants that may be more likely to escape vaccine-induced immunity.
Keywords: CPV-2; CPV-2c; Canine gastroenteritis; New Zealand; canine diseases; haplotype network; molecular survey; parvovirus